STUDIES OF LIPASE AND PHOSPHOLIPASE ENZYMES OBTAINED FROM Tl-IE MEAL OF CITRULLUS VULGARIS OF THE CUCURBITACEAE FAMILY (Biological Sciences - PJSIR, 1999)
The lipase and phospholipase extracted fromthemealof matureseeds of Citrullusvulgarisshowedoptimumactivity at40°Cand pH 7 in aqueous media. N-heptane was found to be themost satisfactory solvent media tomaximize activities of lipaseand phospholipase. The activity of lipase extracted fromgerminated seeds increased with the stage of seeds developmentbut was found to be reverse for the phospholipase activity.